Effect of potential on the early stages of nucleation and properties of the electrochemically synthesized ZnO nanorods. (March 2015) - Henni, A.; Merrouche, A.; Telli, L.; Azizi, A.; Nechache, R.
Abstract: The zinc oxide nanostructured were synthesized on Indium doped tin oxide substrate using cathodic reduction of H2 O2 and ZnCl2 from chloride aqueous electrolyte under differents applied potentials. The effects of this potential on the nucleation of ZnO seeds were investigated by performing transient current measurements and using model based on Scharifker–Hills equations. The results suggest that the nucleation mechanism of ZnO is progressive with a three-dimensional growth of the hemispherical nuclei. The XRD patterns show that the ZnO crystallizes in a hexagonal Würtzite-type structure with a phase preferentially orientated along c -axis. The structural analysis evidences a strong relationship between the directional growth along (0 0 2) crystallographic plane and the applied potentials. ZnO crystalizes in hexagonal nanorods (NRs) with diameters in the ranges of 160–250 nm. Photoelectrochemical study indicates that the obtained films have n-type semiconducting behaviour, and generate high photocurrents up to 40 μA/cm 2 at −1.0 and −1.1 V. The transmittance spectra indicate that the films exhibit a good optical quality with low defects density with an averaged band gap of ~3.31 eV.